Diminished antimicrobial drug use in dogs with allergic dermatitis treated with oclacitinib - Mwacalimba, Kennedy; Hillier, Andrew; Rosenbaum, Michele; Brennan, Christopher; Amodie, Deborah (Frontiers in Veterinary Science, 2023)
Introduction Dogs with allergic dermatitis often suffer concurrent skin and ear infections. The objective of this study was to retrospectively quantify the number of systemic and topical antimicrobial transactions in dogs with allergic dermatitis, following administration of oclacitinib or a glucocorticoid, compared to dogs that did not receive a pruritus therapy when there is an initial diagnosis of pyoderma. A secondary objective was to demonstrate that dogs on oclacitinib use fewer antimicrobials and concomitant therapies over time and have improved quality of life. Materials and methods This was a retrospective case–control study using a large, centralized database to identify canine patients receiving pruritus therapy along with a concurrent diagnosis of pyoderma. For the second objective, 58 client-owned dogs diagnosed with allergic dermatitis were enrolled in a prospective owner and dog quality of life and treatment satisfaction (QoL&TS) study that also evaluated concomitant therapy use over time. In Part A, data consisted of anonymous transaction records from 1,134 hospitals across the United States, representing pyoderma visits between December 2018 and December 2019. Odds ratios comparing the relative odds of having additional antimicrobial agent transactions were calculated, given initial pruritus therapy compared to dogs that did not receive pruritus therapy. Parametric bootstrapping was used to calculate goodness-of-fit statistics. In part B, dogs entered the study on Day 0 and returned for examination on Days 14, 21, 30, and 60. Owner determination of QoL&TS was performed on Days 0, 1, 3, 14, 21, 30, and 60. On Days 0, 14, 21, and 60, a veterinarian assessed concomitant therapies and dermatitis severity scoring. Least Squares Means and Standard Errors for QoL&TS, and Dermatitis Vet VAS (Visual Analog Scale) Scores were calculated using a Linear Mixed Model Approach for Repeated Measures (α = 0.05). The percent reduction in therapies was also calculated. Results Dogs that received oclacitinib (n = 5,132) or a glucocorticoid (n = 7,024) had reduced odds (OR: 0.8091; p = 0.0002 and OR: 0.7095; p < 0.0001, respectively) of having a follow up antimicrobial drug transaction after initial antimicrobial therapy compared to dogs with no pruritus therapy at the initial visit (n = 12,997). In part B, oclacitinib demonstrated a statistically significant improvement in QoL&TS scores over time QoL (p < 0.05). Veterinarian assessment showed a 70% reduction in dermatitis severity over time (p < 0.05), supporting oclacitinib’s anti-inflammatory effects. Oclacitinib therapy was also associated with an 83% reduction in concomitant treatments, including a 100% reduction in systemic antimicrobial therapy over eight weeks. Discussion Dogs receiving oclacitinib showed no increase in antimicrobial therapy transactions compared to glucocorticoid recipients at the initial pyoderma diagnosis. Having a pruritus therapy at the index pyoderma visit reduced the odds of subsequent antimicrobial transactions. In addition to reducing concomitant therapy usage, oclacitinib improved owner and pet QoL, suggesting a paradigm shift in treatment success that could reshape allergic pruritus therapy recommendations. The study provides empirical evidence of oclacitinib’s reduction in antibacterial therapy, supporting its therapeutic value and antimicrobial stewardship.